A simple risk score based on sleep quality for predicting depressive symptoms in menopausal women: a multicenter study. Issue 2 (17th February 2018) - Zheng, Yanwei; Zhou, Yang; Zhu, Jieping; Hua, Qi; Tao, Minfang
ABSTRACT: Objective : We aim to establish a simple risk score based on sleep quality for predicting depressive symptoms in menopausal women through a cross-sectional investigation. Materials and methods : A total of 705 Chinese women aged 40–60 years were included in this cross-sectional investigation of a self-report questionnaire from the Physical Examination Center at Shanghai Jiao Tong University Affiliated Sixth People's Hospital. Depressive symptoms and sleep quality were evaluated using self-rating depressive symptom scale (SDS)and the Pittsburgh Sleep Quality Index (PSQI), respectively. After setting up a logistic regression model and computing the odds ratio value, we further calculated and predicted the risk score for depressive symptoms and then established a risk score system. Finally, we validated the risk score in two investigations (Validation 1 and Validation 2). Results : The risk scoring system for predicting depressive symptoms included a history of cancer, subjective sleep quality, sleep disorder and daytime dysfunction, with total scores ranging from 0–35 points. The receiver operating characteristic (ROC) sample curve was 0.801 (95% CI 0.753–0.848). The Area Under the Curve (AUC) was 0.832 (95% CI 0.738–0.925) in Validation 1 and 0.799 (95%CI 0.667–0.930) in Validation 2. The best cutoff point for depressive symptoms in the sample population was ≥8 points, and the sensitivity and specificity were 0.698 and 0.824, respectively. The sensitivity was 0.775 and 0.667 in Validation 1 and Validation 2, respectively. Conclusions : The risk score for predicting depressive symptoms in menopausal women based on sleep is convenient. Because there is no complex assessment of multiple scales requiredIt may be a preliminary screening tool for depressive symptoms in menopausal women.